Argentina's lost patrol armed struggle, 1969-1979 - Moyano, María José (Yale University Press, 1995)
María José Moyano bases her investigation on an extraordinary collection of personal interviews with guerrillas, political leaders, military leaders, and journalists, as well as extensive readings of sources in four languages. She analyzes not only a decade of some of the bloodiest internal fighting in Argentina's history but also the theoretical underpinnings of violent opposition movements. Moyano argues that after 1973 the guerrilla struggle in Argentina became militarized: due to both internal and external factors, the guerrillas developed a blind adherence to military as opposed to political strategies, lost touch with the political context in which they were operating, and rejected compromise and nonmilitary solutions to conflicts. Moyano's book will be mandatory reading for those interested in the history of this period as well as for students of political violence, terrorism, and repression.